LncRNA SNHG4 promotes tumour growth by sponging miR‐224‐3p and predicts poor survival and recurrence in human osteosarcoma. (28th August 2018) - Xu, Ruida; Feng, Fan; Yu, Xiaosheng; Liu, Zude; Lao, Lifeng
Abstract: Objective: Accumulating data show that dysregulation of long noncoding RNAs (lncRNAs) acts a critical role in a variety of malignancies. Among these lncRNAs, small nucleolar RNA host genes (SNHGs) are associated with tumour growth and progression. But, the molecular mechanisms by which SNHG4 contributes to osteosarcoma remain undocumented. Methods: The association between lncRNA SNHG4 expression and clinicopathologic characteristics and prognosis in patients with osteosarcoma was analysed by TCGA RNA‐sequencing data. Cell viability and colony formation abilities were respectively assessed by MTT and colony formation assays. LncRNA SNHG4‐specific binding with miR‐224‐3p was verified by bioinformatic analysis, luciferase gene report, and RNA immunoprecipitation assays. Regulation relationship between SNHG4 and miR‐224‐3p expression was further evaluated by the rescue experiments. Results: The expression level of lncRNA SNHG4 was significantly elevated in osteosarcoma samples and cell lines as compared with the adjacent normal tissues, and SNHG4 high expression was associated with tumour size (TS) and poor prognosis in patients with osteosarcoma. Knockdown of SNHG4 suppressed cell viability and invasive potential, whereas ectopic SNHG4 expression displayed the opposite effects. Moreover, we found that lncRNA SNHG4 acted as a sponge of miR‐224‐3p, and miR‐224‐3p mimic reversed SNHG4 induced tumour‐promoting effects in osteosarcoma cells. The expression of miR‐224‐3p depicted a negative correlation with SNHG4 in osteosarcoma samples and miR‐224‐3p low expression was associated with TS and poor survival in patients with osteosarcoma. Conclusion: Our findings demonstrated that LncRNA SNHG4 promoted tumour growth by sponging miR‐224‐3p and represented a poor prognostic factor in patients with osteosarcoma.